ABHD7-mediated depalmitoylation of lamin A promotes myoblast differentiation - Yuan Shen; Liang-Liang Zheng; Cai-Yun Fang; Yao-Yao Xu; Chao Wang; Jin-Tao Li; Ming-Zhu Lei; Miao Yin; Hao-Jie Lu; Qun-Ying Lei; Jia Qu (Cell Reports, 2024)
Summary: LMNA gene mutation can cause muscular dystrophy, and post-translational modification plays a critical role in regulating its function. Here, we identify that lamin A is palmitoylated at cysteine 522, 588, and 591 residues, which are reversely catalyzed by palmitoyltransferase zinc finger DHHC-type palmitoyltransferase 5 (ZDHHC5) and depalmitoylase α/β hydrolase domain 7 (ABHD7). Furthermore, the metabolite lactate promotes palmitoylation of lamin A by inhibiting the interaction between it and ABHD7. Interestingly, low-level palmitoylation of lamin A promotes, whereas high-level palmitoylation of lamin A inhibits, murine myoblast differentiation. Together, these observations suggest that ABHD7-mediated depalmitoylation of lamin A controls myoblast differentiation.